2022
DOI: 10.7759/cureus.29849
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neurological Manifestation in Krait Bites Despite Anti-snake Venom Therapy

Abstract: A severe medical emergency that poses a life-threatening risk is envenomation from a snake bite. Among the several snake families, krait bites are known to result in neurological symptoms, including ptosis, headache, and sweating. A 12-year-old adolescent boy who had been bitten by a krait appeared in this instance. The patient showed neurological symptoms after receiving anti-snake venom (ASV). He had three rounds of ASV and made a full recovery. To the best of our knowledge, there have not yet been any repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Successful ventilation with survival to discharge is documented in case reports using SIMV and mandatory pressure-controlled ventilation for Bungarus sp. envenomation ( 61 , 62 ). Volume-controlled mandatory ventilation was compared to adaptive support ventilation in a prospective randomized trial of 48 adults with neuroparalytic snake envenomation; mode did not appear to significantly affect outcome with respect to time to weaning, incidence of VAP or length of hospital stay ( 63 ).…”
Section: Ventilator Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful ventilation with survival to discharge is documented in case reports using SIMV and mandatory pressure-controlled ventilation for Bungarus sp. envenomation ( 61 , 62 ). Volume-controlled mandatory ventilation was compared to adaptive support ventilation in a prospective randomized trial of 48 adults with neuroparalytic snake envenomation; mode did not appear to significantly affect outcome with respect to time to weaning, incidence of VAP or length of hospital stay ( 63 ).…”
Section: Ventilator Settingsmentioning
confidence: 99%
“…A systematic review in humans found early tracheostomy tube placement in patients undergoing MV reduces sedative requirements but does not significantly affect incidence of VAP, duration of MV or mortality ( 143 ). A 1964 study of elapid envenomation described tracheostomy tube placement in 30% (16/52) of affected patients with common complications including minor tracheostomy site hemorrhage (11%, 6/52) tube obstruction and displacement ( 144 ), More recent literature does not report tracheostomy for snake envenomation, so the utility of this procedure in this context is unclear ( 61 , 63 , 64 , 85 , 87 , 89 , 129 , 137 , 144 147 ). Emergency cricothyroidotomy has been described in a person with crotalid envenomation when severe facial and oral oedema prevented successful orotracheal intubation ( 148 ).…”
Section: Weaning From Mechanical Ventilationmentioning
confidence: 99%